Using linguistic, psychosemantic and psychological analysis method in applied research - Victoria V. Dobrova; Irina G. Sysueva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article presents the possible methods of applied interdisciplinary research for personal characteristics of the subjects of verbal communication as one of the most promising areas of research. The analysis methods of such areas of expertise as linguistics, psychology and psychosemantics were proposed and proved to be effective as part of the experiment conducted by the authors. In the first stage the linguistic and psycholinguistic methods might be used. At a later stage methods and techniques of psychological analysis can be successfully applied.